Environment, agroforestry & livestock management - Kundu, S. S.; Pathak, P. S. (Lucknow : International Book Distributing Co., 2008)
Contributed articles with reference to India.
Felicitation volume in honor of P.S. Pathak.
Includes bibliographical references and index.
Keywords: Agroforestry -- India; Range management -- India; Livestock -- India; Natural resources -- India -- Management